Design of a tunable microlens based on hybrid single-wall carbon nanotube and liquid crystal - Seyedeh Nastaran Hosseini; Mohammad Mohammadimasoudi; Farid Khoshkhati; Javad Koohsorkhi (Hybrid Advances)
Tunable liquid crystal (LC) lenses have garnered significant interest in recent years for their lightweight, cost-effectiveness, and versatility in applications like augmented reality, ophthalmic devices, and astronomy. Despite numerous proposed structures to enhance LC lens performance, achieving a minimal focal length while preserving image quality and balancing cost and complexity remains a daunting challenge. Adaptive microlenses encounter these obstacles due to physical constraints and diffraction effects. One promising solution lies in using adaptive LC-carbon nanotubes (CNTs) lenses. By adjusting external stimuli like electric or magnetic fields, it is possible to modify the refractive index distribution of the LC medium, thus changing the focal length of the microlens. When paired with CNTs, the LC molecules' orientation and control of focal length can be even more precise. Our research findings suggest that to achieve the shortest focal length in a microlens with a thickness of 22.5 μm, it is recommended that the diameter of the CNT should not exceed 10 nm, and the height of CNT should fall within the range of 10–20 μm considering the presence of screening effect. Conversely, for a microlens with low full width at half maximum (FWHM), narrower light spot, it is advisable to use CNT with a diameter larger than 100 nm and a height greater than 13 μm. Additionally, for a microlens with an efficient Fresnel number in the range of 1–10, the microlens should have CNT with widths from 100 to 200 nm. Therefore, based on the importance of each factor (focal length, FWHM, and Fresnel number), the dimensions of the carbon nanotube can be selected to suit the desired application.